Co‐delivery of Cisplatin and Chlorin e6 by Poly(phosphotyrosine) for Synergistic Chemotherapy and Photodynamic Therapy. Issue 20 (9th August 2022) - Zhou, Haisen; Wang, Yaoyi; Hou, Yingqin; Zhang, Zhengkui; Wang, Qi; Tian, Xiaodong; Lu, Hua
Comprehensive Summary: Nanoscale drug delivery systems (NDDSs) have emerged as promising carriers for combinational therapy by co‐delivery of multiple drugs and modalities. However, most co‐delivery systems require the use of complicated materials and formulations. Herein, we report the single use of a polymeric material, namely mPEG‐ block ‐poly(phosphotyrosine) (mPEG‐ b ‐PpY), as a multi‐functional carrier for the facile fabrication of NDDS Pt/Ce6@mPEG‐b‐PpY (PtCeNP) for the co‐delivery of cisplatin and photosensitizer chlorin e6 (Ce6) via phosphato‐platinum coordination and π‐π stacking, respectively. PtCeNP improves the solubility, cellular uptake, and bioavailability of both parental drugs, and showed strong synergistic antitumor efficacy both in vitro and in vivo through combined chemo‐photodynamic therapy. Our results indicate that PpY is a biocompatible, multifunctional, and promising carrier material suitable for a variety of drugs and may simplify the design for co‐delivery systems. Abstract : Nanoscale drug delivery systems have emerged as promising carriers for combinational therapy by co‐delivery of multiple drugs and modalities. Herein, we report the single use of a polymeric material, namely mPEG‐block‐poly(phosphotyrosine) (mPEG‐b‐PpY), as a multi‐functional carrier for the facile fabrication of NDDS Pt/Ce6@mPEG‐b‐PpY for the co‐delivery of cisplatin and photosensitizer chlorin e6 via phosphato‐platinum coordination and π‐π stacking, respectively. Our results indicate that PpY is a biocompatible, multifunctional, and promising carrier material suitable for a variety of drugs and may simplify the design for co‐delivery systems.